Perilaku Pemeriksaan Kesehatan Dasar Untuk Mencegah Risiko Penyakit Jantung Pada Lansia - Habeahan, Natamia Kyrieleison; Juniarti, Neti; Mulya, Adelse Prima (UI Scholars Hub, 2024)
Bakground. Various disease courses in the elderly have their own characteristics such as chronicity, severity, and frequent recurrence. One of them is cardiovascular disease which is a degenerative disease. Routine basic health checks to prevent the risk of heart disease in the elderly are very important. However, it is not widely known how the health check behavior of the elderly in the Sumedang area, West Java. Aim. The study aims to identify the proportion of elderly people who conduct regular basic health checks and to find out how many elderly people have a risk of heart disease so that prevention can be done in the elderly so as not to get heart disease. Method. This study used a type of quantitative research with descriptive methods and a cross sectional study approach with a total of 91 respondents. The sample was taken with incidental sampling technique, which is based on coincidence to check blood pressure, blood cholesterol and blood sugar. Result. The distribution of elderly habits in conducting health checks, as many as 52 (57.1%) elderly who routinely conduct health checks every month. There are 41.8% of elderly people suffering from hypertension, 30.8% of elderly people have high blood cholesterol levels, and 11% of elderly people are included in the diabetes category from the results of blood sugar checks. Conclusion. The description of the elderly in Jatinangor, especially Cipacing Village and Cilayung Village, needs to be improved. The results of blood pressure examinations, blood cholesterol levels and abnormal blood sugar levels need to be a concern for health workers in the health center work area.